Prevalence of Shiga Toxin-Producing Escherichia coli (STEC) and Risk Characterization Based on Virulence Genes in Retail Raw Ground Meat of Beef, Veal, and Lamb in Canada - Helen Zhang; Etsuko Yamamoto; Austin Markell; Catherine Carrillo; Annie Locas (Journal of Food Protection)
Shiga toxin-producing Escherichia coli (STEC) are potentially pathogenic E. coli that may cause mild to severe gastrointestinal illnesses. STEC-contaminated foods of animal origin have been the most frequently implicated sources of foodborne outbreaks. A multiyear (2016 to 2021) targeted survey was conducted to investigate the prevalence of STEC in retail ground meats (beef, veal, and lamb). Samples were screened for the presence of Shiga toxin genes (stx) to identify presumptive samples, followed by culture and molecular confirmation of isolates to confirm the presence of stx genes and subsequent characterization by whole-genome-sequencing (WGS) for O serogroup and virulence genes (e.g., stx, eae, aggR). A total of 175 STEC strains were isolated from a total of 148 samples where the presence of viable STEC was confirmed out of 2,398 ground meat samples. This represented 1.2% (7/589 positive, 8 unique strains) of the beef samples, 4.7% (58/1,241 positive, 67 unique strains) of the veal samples, and 14.6% (83/568 positive, 100 unique strains) of the lamb samples. The intimin virulence gene, eae, was identified in the STEC strains of veal origin (9/67, 13.4%) only and were classified as belonging to risk level 1 (1/67), level 3 (2/67), and level 4 (6/67) according to the FAO/WHO risk categories. Risk level 2 STEC strains were of beef (2/8, 25.0%), veal (8/67, 11.9%), and lamb (1/100, 1.0%) origin. The majority of the STEC strains, 75.0% (6/8) of the beef, 67.2% (45/67) of the veal, and 94.0% (94/100) of the lamb STEC strains were classified as risk level 5 (lowest level) of the FAO/WHO risk categories. This study’s findings indicate that the current food safety control measures implemented for ground meats in Canada are effective at maintaining an acceptable level of possible contamination with STEC strains associated with severe clinical outcomes. Continued application of effective control measures and safe food handling practices by consumers will minimize the potential risk of foodborne infections from raw ground meats.